2020
DOI: 10.3389/fphar.2020.593655
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Edible Jujube, the Ziziphus jujuba Fruit: A Heath Food Supplement for Anemia Prevalence

Abstract: The fruits of Ziziphus jujuba, commonly known as jujube, red date or Chinese date, are taken as fresh or dried food, and as traditional medicine worldwide due to high nutritional and health values. Traditionally in China, jujube is considered as a medicinal fruit that is being used in treating blood deficiency. In this review, the beneficial effects of jujubes on the hematopoietic functions are summarized and discussed. As illustrated in cell and animal models, the application of jujube extract possessed benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 73 publications
0
24
0
1
Order By: Relevance
“…Recent pharmaceutic and pharmacodynamics investigations have shown that flavonoids and polysaccharides are major contributors to the antioxidative efficacy of jujube [16][17][18]. In addition, these polysaccharides in jujube are beneficial to human health because of their immuno-modulatory and hematopoietic efficacies [19,20]. Furthermore, the triterpenic acids present in jujube are the main ingredients responsible for their anti-inflammatory and anticancer properties [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmaceutic and pharmacodynamics investigations have shown that flavonoids and polysaccharides are major contributors to the antioxidative efficacy of jujube [16][17][18]. In addition, these polysaccharides in jujube are beneficial to human health because of their immuno-modulatory and hematopoietic efficacies [19,20]. Furthermore, the triterpenic acids present in jujube are the main ingredients responsible for their anti-inflammatory and anticancer properties [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…inermis (Bunge) Rehder, which exhibit anti-inflammatory and cytotoxic activities. Besides, cAMP was found to be abundant in Jujube seed [ 32 ], and Moon et al [ 14 ] determined that spinosin from the seed of Z . jujuba prevents skin pigmentation by inhibiting tyrosinase.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used as a traditional herbal medicine for thousands of years. According to the earliest Chinese medical monograph, Shennong Ben Cao Jing (300 BC−200 AD), JF was considered one of the excellent herbal medicines ( Chen and Tsim, 2020 ). TCM believes that JF has the effect of reinforcing spleen and stomach, and is commonly used for the treatment of anorexia, fatigue and loose stools related to deficiency syndromes of the spleen and of hysteria in woman ( Gao et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%